Differentiated service delivery models among PLHIV in Akwa Ibom and Cross River States, Nigeria during the COVID‐19 pandemic: descriptive analysis of programmatic data. (28th October 2021) - Sanwo, Olusola; Persaud, Navindra E.; Nwaokoro, Pius; Idemudia, Augustine; Akpan, Uduak; Toyo, Otoyo; Imohi, Philip; Badru, Titilope; Obiora‐Okafo, Chika; Uzochukwu, Chimamaka Excellence; Aliu, Oluwapelumi; Olatunbosun, Kolawole; et al.
Abstract: Introduction: The rapid increase in the number of people living with HIV (PLHIV) on antiretroviral therapy (ART) in Akwa Ibom and Cross River states in Nigeria led to overcrowding at clinics. Patients were devolved to receive ART refills through five differentiated service delivery (DSD) models: fast‐track (FT), adolescent refill clubs (ARCs), community pharmacy ART refill programs (CPARPs), community ART refill clubs (CARCs) and community ART refill groups (CARGs) designed to meet the needs of different groups of PLHIV. In the context of COVID‐19‐related travel restrictions, out‐of‐facility models offered critical mechanisms for continuity of treatment. We compared retention and viral suppression among those devolved to DSD with those who continued standard care at facilities. Methods: A retrospective cohort study was conducted among patients devolved to DSD from January 2018 to December 2020. Bivariate analyses were conducted to assess differences in retention and viral suppression by socio‐demographic characteristics. Kaplan–Meier assessed retention at 3, 6, 9 and 12 months. Differences in proportions were compared using the chi‐square test; a p ‐value of <0.05 was considered significant. Results: A total of 40, 800 PLHIV from 84 facilities received ART through the five models: CARC (53%), FT (19.1%), ARC (12.1%), CPARP (10.4%) and CARG (5.4%). Retention rates at 6 months exceeded 96% for all models compared to 94% among those continuing standard care. Among those using DSD, retention rate at 12 months was higher among adults than children (97.8% vs. 96.7%, p = 0.04). No significant sex differences in retention rates were found among those enrolled in DSD. Viral suppression rates among PLHIV served through DSD were significantly higher among adults than children (95.4% vs. 89.2%; p <0.01). Among adults, 95.4% enrolled in DSD were virally suppressed compared to 91.8% of those in standard care ( p <0.01). For children, 89.2% enrolled in DSD were virally suppressed compared to 83.2% in standard care ( p <0.01). Conclusions: PLHIV receiving ART through DSD models had retention but higher viral suppression rates compared to those receiving standard care. Expanding DSD during COVID‐19 has helped ensure uninterrupted access to ART in Nigeria. Further scale‐up is warranted to decongest facilities and improve clinical outcomes.